Penguatan Pendidikan Karakter Melalui Manajemen Pembelajaran - Fathoni, Moh Yusni; Rofiki, Moh (Universitas Nusantara PGRI Kediri, 2023)
This research examines the strengthening of student character education through learning management at MTs Ihyaul Islam Alaspandan. Learning management through the basic functions of planning, organizing, actuating, and controlling to be applied to students in order to make character-educated students will certainly be useful for the progress of the nation and State as well as the ideals of the institution. Both parents need to be considered and endeavored by the institution as one of the efforts that greatly affect the success of students who will become responsible, trustworthy, disciplined, and character-educated leaders in the future. This research uses a qualitative approach of case study type with data collection techniques through participant observation, in-depth interviews, and documentation. The results of research on strengthening character education through learning management at MTs Ihyaul Islam Alaspandan use the essential functions of learning management planning, organizing, actuating, and controlling the character education of amal ma'ruf, nahi mungkar, hablun min Allah and hablun min annas students.